Clarification on the name-bearing type designation of several cyclophorid species (Mollusca, Gastropoda) by H. H. Godwin-Austen (1915) - Jirapatrasilp, Parin (Zookeys, 2021)
The type series boundary and the name-bearing type designation of each cyclophorid taxon originally described by Godwin-Austen are clarified based on an interpretation that complies with the ICZN. Previous statuses of type specimens designated by previous authors are reconsidered. Lectotypes of Spiraculum oakesi Godwin-Austen, 1915, Spiraculum kempi Godwin-Austen, 1915, Pterocyclos aborensis Godwin-Austen, 1915, Pterocyclos miriensis Godwin-Austen, 1915, Pterocyclos brahmakundensis Godwin-Austen, 1915, Spiraculum luyorensis Godwin-Austen, 1915, Spiraculum putaoensis Godwin-Austen, 1915, and Theobaldius oakesi Godwin-Austen, 1915 are here designated to stabilize the existing nomenclature. In addition, the type specimens of Pterocyclos miriensis and Theobaldius oakesi are photographed and figured for the first time.